Interest rate ceiling and financial sustainability of microfinance institutions in Zambia - Kambole, Christopher Ngolwe (Research of GSB, 2018)
Interest rate ceilings are often considered as an effective way of preventing lenders from charging extortionate interest rates. However, setting the rates too low may cause institutions to fail to raise enough revenue to cover their costs. Low rates may pressure MFIs to reduce costs, increase loan sizes, withdraw services from areas where it is expensive to operate, or exit from the market altogether. A 42% interest rate ceiling was introduced in Zambia on the effective annual lending interest rate of MFIs in January 2013, which was later removed in November 2015. This research was aimed at investigating the effect of interest rate ceiling and microfinance direct costs on the financial sustainability of microfinance institutions in Zambia. The study used time series data from consolidated quarterly financial statements from March 2006 to September 2016 and employed Autoregressive Distributed Lags (ARDL) approach to analyse the effect of Yield on Gross Portfolio, Cost of Funds, Operating Expenses and Loan Loss provisions on Operational Self Sufficiency (OSS). OSS was used as a proxy for financial sustainability (dependent variable). Results of the time series analyses showed a positive and significant effect of Yield on Gross Portfolio and Cost of Funds on OSS in the long run. On the other hand, Operating Expenses and Loan Loss provisions had a negative relationship with OSS, albeit statistically insignificant. Trend analysis of the Yield on Gross Portfolio showed a downward trend and consequently the OSS also trended downwards, with the lowest OSS being recorded during the period interest rate ceilings were introduced. However, the trend showed that the microfinance sector was generally sustainable during the study period. The reduction in OSS following the introduction of the ceiling confirmed findings from prior studies regarding the negative impact of interest rate ceilings on the financial sustainability of MFIs. Although the study results showed that the MFIs were generally sustainable during the study period, it was evident that they were negatively impacted by the interest rate ceiling. Therefore the recommendation from this study is that interest rates must be set at levels where costs can be adequately covered. Furthermore, managing costs and loan delinquency should be core priorities among Zambian MFIs to ensure financial sustainability.